2011
DOI: 10.1371/journal.pgen.1002390
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Evolutionarily Conserved Exons as Regulated Targets for the Splicing Activator Tra2β in Development

Abstract: Alternative splicing amplifies the information content of the genome, creating multiple mRNA isoforms from single genes. The evolutionarily conserved splicing activator Tra2β (Sfrs10) is essential for mouse embryogenesis and implicated in spermatogenesis. Here we find that Tra2β is up-regulated as the mitotic stem cell containing population of male germ cells differentiate into meiotic and post-meiotic cells. Using CLIP coupled to deep sequencing, we found that Tra2β binds a high frequency of exons and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(142 citation statements)
references
References 69 publications
7
135
0
Order By: Relevance
“…The functional importance of RS1 domain in spatial organization is supported by a recent finding that removal of the RS1 domain completely disabled Tra2␤-mediated splicing activation of the physiological target exons (47). In addition, we observed that GFP-Tra2␤ and GFP-RS1RRM were concentrated in nuclear speckles with a diffusive distribution in the nearby nucleoplasm (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The functional importance of RS1 domain in spatial organization is supported by a recent finding that removal of the RS1 domain completely disabled Tra2␤-mediated splicing activation of the physiological target exons (47). In addition, we observed that GFP-Tra2␤ and GFP-RS1RRM were concentrated in nuclear speckles with a diffusive distribution in the nearby nucleoplasm (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Up-regulation of TRA2β promotes several splicing switches, including in CD44, which were previously associated with tumor progression and metastasis (Watermann et al 2006). Another example of a TRA2β splicing target is the nuclear autoantigenic sperm protein NASP, which is important for cell survival (Grellscheid et al 2011). TRA2β also regulates splicing of the estrogen receptor α, decreasing the expression of the ERaΔ7 isoform, which correlates with a better outcome in endometrial cancer (Hirschfeld et al 2015).…”
Section: Tra2β-transformer 2β Homolog (Drosophila)mentioning
confidence: 99%
“…4D; Grellscheid et al 2011). Considering that "AGAA" shared 1 nt with the downstream PAS "ATTAAA" in the alternative 3 ′ UTR of Rras2, we mutated the first 3 nt to avoid disruption of the PAS ("AGAA" to "CCCA") (designated Mut3 in Fig.…”
Section: Global Lengthening Of 3 ′ Utrs Couples With Decreased Gene Ementioning
confidence: 99%